Réflexions sur l'usage des modèles dans les études de transports et les sciences sociales - Dobruszkes, F; Marissal, P (Elsevier, 2002)
The mathematical modelling of human behaviours is extremely common in both theoretical and applied transport studies. This paper begins with an attempt to demonstrate the limits which apply to the reconstruction of a human reality (in this case an origin-destination matrix) by means of a straightforward and commonly used model, the gravity model. These limits stem from the fact that economic, social and political factors and historical aspects are ignored. The reasons for the prevalence of models in transport studies are then discussed as are the consequences of this prevalence: perpetuation of a view of the operation of society which is far from being without political implications, the surrender of the political community to experts, pseudo-scientific justifications for projects for which politicians do not wish to take responsibility.